Cannabidiol and Depression: Promise and Challenge in Building an Evidence Base - Moser, Amelia D.; Batt, Melissa M.; Bidwell, Lorna C.; Kaiser, Roselinde H. (Adolescent Psychiatry, 2023)
Background: Interest in the potential mental health effects of cannabidiol (CBD) has increased recently, with a surge in commercial and pharmaceutical development of CBD products and a concomitant rise in consumer use. However, despite the widespread and growing use of CBD products by adults and adolescents, the mental health effects of CBD remain largely unknown.Objective: The goals of this review are: 1) to briefly review the evidence base for the mental health effects of CBD, using depression as an exemplar, and 2) to systematically outline complementary study designs needed to test CBD effects, together with challenges and special considerations related to each design.Methods: This review integrates empirical findings related to CBD's effects on mental health outcomes with the literature on intervention trial design and current legal regulations pertaining to CBD.Conclusion: Complementary controlled and observational studies of CBD are necessary to substantiate claims of mental health benefits, including for clinical depression and in pediatric populations. Investigators must consider challenges and opportunities specific to CBD as an intervention, including legal regulations, commercial or pharmaceutical product choice, dosing and bioavailability, and safety.
Keywords: observational study